Pengembangan Aplikasi E-Voucher Dalam Rangka Efisiensi Penggunaan Bahan Bakar Minyak Di Lingkungan Pemerintah Kota Kupang - Max Lenggu; Yanuar Dally (Jurnal Inovasi Kebijakan, 2021)
In this study, an Application for Fuel Oil Voucher (BBM) will be developed, specifically for official vehicles within the city of Kupang. The application dashboard, which is named Si-Hebat BBM, is placed in the Finance Section of the Kupang City Government, Si-Hebat BBM was developed to minimize the misuse of the current BBM coupons which are still distributed to each OPD manually. The development of the Si-Hebat application is intended to assist the Kupang City government in overcoming the problem of using BBM efficiently and effectively, as well as being controlled digitally, so as to prevent the misuse of coupons and more importantly minimize budget wastage. The Si Hebat BBM application will issue a QR Code containing the identity of the official vehicle, then the QR Code will be affixed to each official vehicle. When the official vehicle enters the gas station, the officer will scan the QR Code which has been connected online to the finance department, so that the filling data can be controlled in real time.